Earth's history. (Milwaukee, WI : Gareth Stevens Pub., 2004)
Explores the history of planet Earth, from its fiery beginnings to the present.
Originally published: Shift. Bethesda, Md. : Discovery Enterprises, c2000.
Keywords: Geology -- Juvenile literature; Geology; Earth -- History -- Juvenile literature; Earth -- History